The protective capability of Hedyotis diffusa Willd on lupus nephritis by attenuating the IL-17 expression in MRL/lpr mice - Li, Ying; Ding, Tao; Chen, Jing; Ji, Jinjun; Wang, Weijie; Ding, Bin; Ge, Weihong; Fan, Yongsheng; Xu, Li (Frontiers in Immunology, 2022)
Lupus nephritis (LN), the most severe organ manifestation of systemic lupus erythematosus (SLE), is generally treated with glucocorticoids (GC) in clinical practice, leading to drug resistance and adverse effects in the long term. Fortunately, the combination of GC and traditional Chinese medical prescriptions can attenuate the adverse effects and improve therapeutic efficiency. Hedyotis diffusa Willd (HDW) is one of the most commonly used herbal compounds for LN treatment, which exhibits “heat-clearing” and “detoxification” effects. However, the underlying pharmacological mechanism remains unclear. The present study identified the chemical compounds in HDW extract with UPLC-Q-TOF-MS/MS. A total of 49 components were identified in the HDW extract, and the IL-17 signaling pathway was highly enriched by network pharmacological analysis. MRL/lpr model mice, reflecting the spontaneous development of LN, were used to evaluate the protective activity and investigate the underlying mechanism of the combination treatment. The white blood cell content (WBC), including lymphocytes and neutrophils, cytokines (IL-6, MCP-1, TNF-a), and various autoantibodies (ANA, ab-dsDNA, ab-snRNP/sm) in the blood of MRL/lpr mice were significantly improved by the intragastric administration of HDW. Additionally, the expression of STAT3, IL-17, Ly6G, and MPO in the kidney and neutrophil NETosis were ameliorated with HDW treatment. The pathological and morphological analysis suggested that HDW application could reduce urinary protein levels and inflammatory cell infiltration and inhibit glomerular interstitial cell proliferation. Hence, HDW might ameliorate lupus nephritis by inhibiting IL-6 secretion and STAT3-induced IL-17 expression. The active compounds in HDW were predictively selected with computational methods. The docking affinity of asiatic acid, neoandrographolide to IL-6, glycyrrhetinic acid, oleanolic acid, ursolic acid, and wilforlide A to STAT3 are extremely high. In conclusion, the IL-6 and STAT3/IL-17signaling pathways could be critical regulative targets of HDW on LN.